Digital social listening in COVID-19 pandemic for informed interventions in the Republic of Moldova: integrated data (One Health & Risk Management, 2023)
Introduction. Social Listening is a suitable tool used in monitoring and controlling the infodemic, a phenomenon that has exacerbated the global public health crisis generated by the COVID-19 pandemic. The purpose of the study. Digital monitoring of public perceptions of the COVID-19 in the Republic of Moldova, evaluating the temporal sequence of message content on social media to understand and inform decision-makers on the necessary actions based on needs/problems. Material and methods. The Talkwalker software, developed for marketing research, has been adapted to the study objective by creating a search syntax for COVID-19. The taxonomy for COVID-19 conversations developed and validated by Purnat et al. was taken into account. Results. Between 01.01-30.11.2022, 18000 results were shared. Interest is expressed through a downward fluctuating curve, the highest audience engagement rate being generated by the Unica.md post regarding the French authorities' decision to waive restrictions (2400 shares, over 155 thousand likes, 521 comments). The aggregate sentiment of netizens is predominantly neutral and negative, dominated by anger and fear.Conclusions. It is observed that the population shows distrust regarding the reality of the pandemic, being reserved towards actions taken by authorities to counter the pandemic, and/or conspiratorial beliefs, which indicate the presence of falsehoods in social media and the need for targeted responses from authorities to increase the population’s resistance to misinformation.